2019
DOI: 10.1002/pen.25107
|View full text |Cite
|
Sign up to set email alerts
|

Insight on the influence of nano zinc oxide on the thermal, dynamic mechanical, and flow characteristics of Poly(lactic acid)– zinc oxide composites

Abstract: Composites of Poly(lactic acid) (PLA) and spherical zinc oxide (ZnO) nanoparticles were prepared using melt processing followed by injection molding. The effect of nanosized ZnO on the molecular structure, thermal properties, dynamic mechanical properties, and flow characteristics of PLA composites were analyzed. Scanning electron microscopy images illustrated the formation of ZnO aggregates through PLA matrix. The molecular weight of PLA-ZnO experienced a substantial decline by 55%, suggesting the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
4
12
0
Order By: Relevance
“…Indeed, within the first studies it was stated out by us that the addition of untreated ZnO NPs into PLA, at melt-processing temperature, led to the severe degradation of the polyester matrix, a process well-determined by ZnO loading. Likewise, the same conclusion was also shared by other research groups [ 26 , 27 ]. However, by considering the high effectiveness of Zn-based products (such as untreated ZnO) to trigger PLA degradation [ 28 ], other researchers have preferred to use the solvent casting method to produce PLA–ZnO nanocomposites [ 16 , 29 ].…”
Section: Introductionsupporting
confidence: 80%
“…Indeed, within the first studies it was stated out by us that the addition of untreated ZnO NPs into PLA, at melt-processing temperature, led to the severe degradation of the polyester matrix, a process well-determined by ZnO loading. Likewise, the same conclusion was also shared by other research groups [ 26 , 27 ]. However, by considering the high effectiveness of Zn-based products (such as untreated ZnO) to trigger PLA degradation [ 28 ], other researchers have preferred to use the solvent casting method to produce PLA–ZnO nanocomposites [ 16 , 29 ].…”
Section: Introductionsupporting
confidence: 80%
“…This thermal degradation is even more exacerbated by the presence of ZnO nanorods. In this case, zinc compounds are known to catalyse both the intermolecular transesterification reactions, leading to PLA with lower molecular weights, and the “unzipping” depolymerization [ 42 , 52 ] with the selective formation of lactide. On the contrary, when Zn-based compounds are absent, PLA degradation can be considered the result of a competition between the random chain scission via a cis-elimination reaction and the cyclic rupture via intramolecular transesterification of the molecules.…”
Section: Resultsmentioning
confidence: 99%
“…14,46 With recent advancements in nanotechnology, nanosized zinc oxides are among the emerging high-value inorganic products with significant features, (such as, high catalyst effect, effective antibacterial properties, high UV absorption, high thermal and physical stability, and high heat capacity) that have many applications in different industries, such as, cosmetics, plastics, sensors, and semiconductors. [47][48][49] It is common to use high concentration of inorganic mineral fillers, such as, Al(OH) 3 up to 20 wt% to modify flame retardancy of polyvinyl chloride (PVC). 50 However, it is reported that the addition of only 0.635 wt% of ZnO and 9 wt% of Al(OH) 3 combination into PVC can significantly increase the LOI value of PVC nanocomposite (up to 30%).…”
Section: Zinc Oxidementioning
confidence: 99%
“…51 This observation was more likely due to the formation of crosslinked surface modified ZnO in polymer matrix, which accelerate the nucleation process and improve the heterogeneous nucleating ability in the cross linked polymer matrix. 48 Intumescent flame retardant systems (IFRs) are FRs that can insulate materials during combustion through the formation of an expanded carbonized layer. These systems usually require three components: an acidic source, a carbonization source, and a blowing agent.…”
Section: Zinc Oxidementioning
confidence: 99%